Heart in art: cardiovascular diseases in novels, films, and paintings - Kaptein, Ad A. (Philos Ethics Humanit Med, 2020)
BACKGROUND: Understanding representations of disease in various art genres provides insights into how patients and health care providers view the diseases. It can also be used to enhance patient care and stimulate patient self-management. METHODS: This paper reviews how cardiovascular diseases are represented in novels, films, and paintings: myocardial infarction, aneurysm, hypertension, stroke, heart transplantation, Marfan’s disease, congestive heart failure. Various search systems and definitions were used to help identify sources of representations of different cardiovascular diseases. The representations of the different diseases were considered separately. The Common Sense Model was used a theoretical model to outline illness perceptions and self-management in the various identified novels, films, and paintings. RESULTS: Myocardial infarction followed by stroke were the most frequently detailed diseases in all three art genres. This reflects their higher prevalence. Representations ranged from biomedical details through to social and psychological consequences of the diseases. CONCLUSIONS: Artistic representations of cardiovascular diseases reflect cognitions, emotions, and images of prevalent disease. These representations shape views and behaviour of ill and healthy persons regarding heart diseases. As these representations are amenable to change, they deserve further research, which may be instrumental in improving the quality of life of persons struck by cardiovascular diseases. Changing illness perceptions appears to be a method to improve self-management and thereby quality of life in patients with various cardiovascular diseases.